New synonymy in Ptychanthus striatus (Lejeuneaceae, Marchantiophyta) - Wang, Jian; Gradstein, Stephan Robbert; Daniels, Albert Ebenezer Dulip; Zhu, Rui-Liang (Phytotaxa, 2014)
Morphological and molecular evidence shows that Spruceanthus wiggintonii A.E.D.Daniels, K.C.Kariyappa & P.Daniel from southern India is a synonym of the widespread Ptychanthus striatus (Lehm. & Lindenb.) Nees.